-(3b+4)=-4b

Simple and best practice solution for -(3b+4)=-4b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3b+4)=-4b equation:


Simplifying
-1(3b + 4) = -4b

Reorder the terms:
-1(4 + 3b) = -4b
(4 * -1 + 3b * -1) = -4b
(-4 + -3b) = -4b

Solving
-4 + -3b = -4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '4b' to each side of the equation.
-4 + -3b + 4b = -4b + 4b

Combine like terms: -3b + 4b = 1b
-4 + 1b = -4b + 4b

Combine like terms: -4b + 4b = 0
-4 + 1b = 0

Add '4' to each side of the equation.
-4 + 4 + 1b = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 1b = 0 + 4
1b = 0 + 4

Combine like terms: 0 + 4 = 4
1b = 4

Divide each side by '1'.
b = 4

Simplifying
b = 4

See similar equations:

| f(x)=0.9(0.6) | | y^2-16y-10=26 | | cos*2x-5*cosx+3=0 | | 6x^2-17x+1=0 | | 7x-2y+5=0 | | 4n-12.4=-6.8 | | y^2=2y+35 | | sin(12x)-sin(6x)=0 | | 9w-8w+4=0 | | -32x--48=-33-5x | | 6x-6x=10 | | (8+x)-3=56 | | n-10=-18 | | (B^8c^6d^5)*(7b^6c^2d)= | | -1-3x=8(x-7) | | 3w-8w+4=0 | | (y^2)-2y-35=0 | | 5x^2+13+8=0 | | x^2+8x-3=06 | | logx(6x-9)=2 | | (-2u^2)*(6u^6)= | | 2x-6+15x=11 | | 7q+11=10q-10 | | 3x^4+27x=0 | | 16+10=13+10 | | -28=5(8f-6) | | 13+10=16+10 | | 2(w+3w)=4(3w+1) | | -15n^5+21n=0 | | 3(2y-8)=-29+9y | | x-3.5=4.2 | | X^2+4x+5=13 |

Equations solver categories